Assessing extranet effectiveness : tools for managing the cost of quality. - Ng, Shang Lim. (2008)
This empirical study uses the SERVQUAL [Parasuraman et al 1985] model as an instrument to explore the following questions in measuring service quality in online business-to-business applications: UTILITY: Is SERVQUAL useful for measuring service quality in this B-to-B context? STRUCTURE: How do the SERVQUAL model's dimensions apply to this context? CONGRUENCE: Do service providers and customers view quality the same way? UNIVERSALITY: Do perceptions of B-to-B service experiences vary across industries?